AKSJOLOGICZNE PRZESŁANKI SPORÓW O MODEL TRANSFORMACJI GOSPODARKI - Marczuk, Stanisław (Wydział Prawa i Administracji UAM, 1999)
The Author discusses the role of axiological factors in the examination of economic phenomenons and more particularly - the role of capacity to reconcile the values of universalism with the facts due to a particularism. In a description of successive theoretical models of capitalism - special attention was devoted to post-modernist, Anglo-American and Rhine types of it. When drawing up axiological background of general view of the market economy in the Illrd (i.e.: present) Republic of Poland, the Author stresses a crisis of moral ties in all post-communist countries, the big impact of famous Polish trade-union „Solidarity” ideas and - finally - discusses reasons of a divergence in obtained appreciations of the adopted transformation model. Also problems involved with the attempt to create some social-welfare State after the example of western market economies are being characterized in the article.
AXIOLOGICAL PREMISES OF CONTROVERSY ABOUT THE MODEL FOR ECONOMY TRANSFORMATION